2019
DOI: 10.3390/ijerph16122138
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the Maturity Status of the Tibial Tuberosity by Ultrasonography in Higher Elementary School Grade Schoolchildren

Abstract: This study aimed to obtain screening data on the maturity status of the tibial tuberosity in schoolchildren of higher elementary school grades for risk management of Osgood–Schlatter disease (OSD). The maturity stages and cartilage thicknesses at the tibial tuberosity were determined by ultrasonography on the occasion of a school-based musculoskeletal examination for 124 grade 5–6 elementary schoolchildren, and their associations with the students’ demographic characteristics and OSD were examined. The time-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The prevalence of OSD ranges from 6.8% to 33% [ 13 , 14 , 15 ], affecting 1 in 10 athletic adolescents [ 3 ], and depends on factors such as the degree of development, the sport discipline or the presence of preventive programs [ 6 ]. For example, Lucena et al found a prevalence of 9.8% among males and females (mean age 13.7 years) [ 8 ], while Kujala et al reported a prevalence of 12.9% (mean age: 13.1 years) [ 9 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of OSD ranges from 6.8% to 33% [ 13 , 14 , 15 ], affecting 1 in 10 athletic adolescents [ 3 ], and depends on factors such as the degree of development, the sport discipline or the presence of preventive programs [ 6 ]. For example, Lucena et al found a prevalence of 9.8% among males and females (mean age 13.7 years) [ 8 ], while Kujala et al reported a prevalence of 12.9% (mean age: 13.1 years) [ 9 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…This fact could be explained due to the fact that girls reach the bone maturation stage of the tibial tuberosity two years earlier than boys [ 16 ]. Furthermore, some authors suggest that the risk of developing OSD is higher among females during the epiphyseal stage, particularly among sports practitioners [ 15 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Finally, between the ages of 14 to 16 years, a complete ossi cation of the remaining insertional cartilage occurs. Previous studies have shown that this maturation process begins earlier in girls which tend to progress 1 to 2 years earlier to the maturity stage than boys [3,8,9]. The offset in bone growth between boys and girls may be related to the development of secondary sex characteristics.…”
Section: Discussionmentioning
confidence: 94%
“…OSD is usually a self-limiting disease and symptoms tend to resolve with simple conservative treatment or at the end stages of skeletal growth [3,15]. Development of OSD during the growth period may be related to the structural changes of the tibial tuberosity before epiphyseal closure which makes it more vulnerable to traction injuries [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…Osgood-Schlatter disease (OSD) is a traction apophysitis characterized by pain, swelling, and bony bump on the anterior aspect of the tibial tuberosity where the patellar tendon inserts into the bone [ 1 , 2 ]. The prevalence of OSD is approximately 10% in adolescents, with 30% having bilateral symptoms [ 3 ], and it may be higher in those who are active in sports [ 4 ].…”
Section: Introductionmentioning
confidence: 99%